Spatial Data Infrastructure and INSPIRE - Tonchovska, Rumyana (World Bank, Washington, DC, 2014)
Spatial Data Infrastructure (SDI) is defined as a framework of policies, institutional arrangements, technologies, data, and people that enables the sharing and effective usage of geographic information by standardizing formats and protocols for access and interoperability. The goals of SDI are to: 1) reduce duplication of efforts among governments, 2) lower costs related to geographic information while making geographic data more accessible, 3) increase the benefits of using available spatial data, and 4) establish key partnerships between states, counties, cities, academia, and the private sector. SDI should be seen as part of wider e- Government initiatives. Infrastructure for Spatial Information in the European Community (INSPIRE) is a European Union (EU) directive that came into force on May 15, 2007, binding EU members to establish a spatial data infrastructure via the Internet that facilitates the sharing of geographic information in a standardized way. INSPIRE addresses technical and nontechnical issues, ranging from standards, organizational and procedural issues, and data policies, to the creation and maintenance of electronic services. INSPIRE is a legal framework for developing SDI throughout the EU in order to facilitate interoperability, that is, the improvement and sharing of information across various levels of government in all EU countries.